Teacher students' meaningful learning in widening learning worlds - Aarto-Pesonen, Leena; Piirainen, Arja (Teaching education (Columbia, S.C.), 2020)
This qualitative metasynthesis investigated students' meaningful learning experiences amid andragogical teacher education programmes. The programmes catered to the specific learning needs of adult students in the context of university-based teacher education. This study aimed to provide a wider picture of the frames of students' meaningful learning in andragogical teacher education programmes. The findings revealed three major learning worlds of adult students' meaningful learning, which formed a common system widening from the professional awakening to the transformative community and agency in society. Based on the findings, this study argues that in andragogical teacher education, which emphasises collaboration and networking in accordance with the current trend in higher education, teacher students may become empowered participants and active agents in society. The findings can be used in planning curricula, and developing programmes of higher education in general and teacher education in particular.